The differences study between wild and aquaculturc gealthead sea bream Sparus aurata L. 1758. I: The morphological differences study between wild and aquaculture gealthead sea bream - Al-saady, Hussain A.; Abu Elela, Refaat G.; Ali, Haneen M. (Al-Mukhtar Journal of Sciences, 2009)
The current study was carried out to eval uate the effect of the en vironmental strees on gilthead sea bream Sparus aurata L during the domestication period in marine aquaculture. More than 50 morphological characters had been studied. There are significant differences between wild and aquaculture S. aurata in some morphological characters such as: eye vertical diameter, distance from the anterior low jaw to eye, distance. from eye to the end of opercle, body width at the initial of dorsal fin, the tail length, distance from lateral line to dorsal fin, body depth at base of caudal fin, the base length of dorsal fin, the base length of anal fin, dorsal fine length, caudal fin length, number of lateral line scale, number of small gill rackers of first gi lis arch, number of large gill rackers of second gills arch. Some variation had been found in calor of the two fishes: in aquaculture fish the gray calor replaced the golden calor of the wild fish with absence of reddish patch on the opercle of wild fish. Also the golden calor at the wild vertex between the eyes turned to gray calor in aquaculture fish. There are some differences in the mouth region between the wild and aquaculture fish, the upper jaw was protruding from the lower jaw in aquaculture fish compared with equal shape in wild fish. There are some incisions and grooves found in one and absent in another. Also some variations were found in the shape ofthe opercle parts of wild and aquaculture fish. The aquaculture fish varied from wild in shape and annuli 01 circuli of scales and in spine ofdorsal and anal fins. as well in the shape and composition of trunk vertebral.